2012
DOI: 10.1183/09031936.00092111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the asthmatic allergen challenge response by the CRTH2 antagonist OC000459

Abstract: CRTH2 (chemoattractant receptor expressed on T-helper (Th) type 2 cells) is a Gprotein-coupled receptor expressed by Th2 lymphocytes and eosinophils that mediates prostaglandin (PG)D 2 -driven chemotaxis. We studied the efficacy of the oral CRTH2 antagonist OC000459 in steroid-naïve asthmatic patients.A randomised, double-blind, placebo-controlled, two-way crossover study of 16 days' treatment with OC000459 (200 mg twice daily) on the late (LAR) and early (EAR) asthmatic responses to bronchial allergen challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 26 publications
(38 reference statements)
3
79
0
Order By: Relevance
“…In the study of OC000459 in steroid-naïve patients with asthma, the CRTH2 antagonist achieved a statistically significant improvement in the FEV 1 in the per-protocol analysis compared with placebo (7.66% predicted [95% confidence interval (CI): 0.49e14.82] or 200 mL) but not in the intention-to-treat population (2.44% predicted [95% CI: 4.42e9.31] or 80 mL) [6]. A separate study of OC000459 resulted in attenuation of the late-phase, but not the early-phase, response to allergen challenge following bronchial challenge in sensitive individuals [10]. Studies performed in patients sensitive to grass pollen [11] have also demonstrated that OC000459 can reduce nasal and ocular symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…In the study of OC000459 in steroid-naïve patients with asthma, the CRTH2 antagonist achieved a statistically significant improvement in the FEV 1 in the per-protocol analysis compared with placebo (7.66% predicted [95% confidence interval (CI): 0.49e14.82] or 200 mL) but not in the intention-to-treat population (2.44% predicted [95% CI: 4.42e9.31] or 80 mL) [6]. A separate study of OC000459 resulted in attenuation of the late-phase, but not the early-phase, response to allergen challenge following bronchial challenge in sensitive individuals [10]. Studies performed in patients sensitive to grass pollen [11] have also demonstrated that OC000459 can reduce nasal and ocular symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Oxagen has presented positive clinical data in an allergen challenge study in steroid-naïve asthmatics [21] and in a larger 4-weeks study in steroid-free moderate persistent asthmatics [22] and are currently running a Phase III asthma study in Russia and also a Phase II study in atopic dermatitis (as Atopic Therapeutics).…”
Section: Expert Opinionmentioning
confidence: 98%
“…Phase 2 studies of the effects of novel anti-inflammatory drugs could be performed in this population, because the high-dose allergen challenge model could provide very important information on the potential effectiveness of these drugs on allergic Table 2 Sputum cell counts at baseline and after high-dose allergen challenge (n = 13) Table 3 Sputum cell counts after low-dose allergen challenge (n = 10) inflammation when administered in addition to ICS. There are a number of novel therapies in development that target Th2 inflammation, such as anticytokine monoclonal antibodies and small molecule inhibitors, such as chemoattractant receptor expressed on T-helper type 2 (CRTh2) antagonists [34][35][36][37]. The potential therapeutic effectiveness of these therapies can be tested at an early stage of clinical development in a small number of subjects using the model and end-points described here.…”
Section: Figurementioning
confidence: 99%